2023
DOI: 10.3390/nu15051151
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Osteoporosis among Patients with Inflammatory Bowel Disease—Do We Already Know Everything?

Abstract: Introduction: There are many known risk factors for osteoporosis (OST) among patients with inflammatory bowel disease (IBD), one of which is physical activity. Material and methods: The aim of the study is to assess the frequency and risk factors of OST among 232 patients with IBD compared to a group of 199 patients without IBD. The participants underwent dual-energy X-ray absorptiometry, laboratory tests, and completed a questionnaire about their physical activity. Results: It was found that 7.3% of IBD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Geerling et al [45], Kallel et al [62], and Akbulut et al [63] reported significantly lower serum vitamin B12 concentrations in CD patients compared to HSs. Valentini et al [46] showed similar vitamin B12 deficiencies in CD patients in remission (9.6%) and HSs (0.0%) [30,43]. Contrary to this report, Yakut et al [61] demonstrated a significantly higher rate of vitamin B12 deficiency in CD patients (22.2.%) compared to controls (7.5%) [21,61].…”
Section: Vitamin B12mentioning
confidence: 74%
See 2 more Smart Citations
“…Geerling et al [45], Kallel et al [62], and Akbulut et al [63] reported significantly lower serum vitamin B12 concentrations in CD patients compared to HSs. Valentini et al [46] showed similar vitamin B12 deficiencies in CD patients in remission (9.6%) and HSs (0.0%) [30,43]. Contrary to this report, Yakut et al [61] demonstrated a significantly higher rate of vitamin B12 deficiency in CD patients (22.2.%) compared to controls (7.5%) [21,61].…”
Section: Vitamin B12mentioning
confidence: 74%
“…It is associated with a lower level of osteocalcin, which increases patients' risk for osteoporosis. The correct level of vitamins D and K2 is a perquisite for achieving a higher concentration of osteocalcin [30]. In a study by Lewandowski et al [30], the abovementioned theory was partially supported by the low serum concentration of vitamin D (14.60 ng/mL) [30].…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various aforementioned complications in IBD, osteoporosis constitutes a significant medical problem with a prevalence of 18 to 42% [ 5 , 6 ]. Osteoporosis is an undesirable condition because it leads to an increased risk of non-traumatic fractures, which are associated with significant morbidity and mortality and impose an additional financial burden on the healthcare system [ 7 ]. The etiology of bone loss in IBD involves several factors that can roughly be divided into a group of variables primarily associated with general skeletal health, such as low mineral intake, decreased vitamin D synthesis, and physical activity, and IBD-associated factors, including harmful effects of prolonged administration of corticosteroids and gastrointestinal damage as a result of an unceasing inflammatory process [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, environmental factors appear to play a role in the illness. IBD increases the chances of developing other illnesses, such as colorectal cancer [ 7 ] and osteoporosis [ 8 ]. More than 7% of patients with IBD develop osteoporosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%